Family planning needs to limit childbearing are unmet, yet our parity is high: characterizing and unveiling the predictive factors - A. S. Adebowale; M. E. Palamuleni (BMC, 2023)
Abstract Background The unmet need for limiting childbearing (UNLC) remains a problem in Nigeria. Conception after four pregnancies is considered a high-risk pregnancy. We examined the level, reasons for non-use of contraception, and predictors of UNLC among high parity (≥ 4 live birth) women in Nigeria. Methods This cross-sectional design study was based on the analysis of nationally representative weighted data (2018 Nigeria Demographic Health Survey). The study focused on high-parity women of reproductive age (n = 4260) who do not want to have any more children irrespective of the number of their surviving children. Multi-stage cluster sampling approach was used for sample selection. Data were analyzed using logistic regression (α0.05). Results Mean age of the respondents and children ever born was 38.92 ± 5.7 and 6.54 ± 2.3 respectively. The prevalence of UNLC was 40.9%, higher in the rural (48.8%) than urban (32.8%) areas, highest among women with no formal education (52.0%), higher among Muslims (48.4%) than Christians (34.8%), highest in the North-West (51.7%) and least in the South-East (26.1%). The most reported reasons for non-use of family planning (FP) were; respondents opposed (25.0%), infrequent sex (15.0%), fatalistic (13.2%), husband/partner opposed (11.2%), fear of side effects/health (8.5%), and religious prohibition (3.3%). The odds of UNLC was 100% higher among women aged 40-49 years compared to the younger women in age group 20-29 years. Living in the rural area predisposes high parity women of reproductive age to higher risks of UNLC (OR = 1.35, 95% C.I = 1.14-1.59, p < 0.001). Lack of access to family planning information through health workers (OR = 1.94, 95% C.I = 1.63-2.30, p < 0.001) increased the risks of UNLC. Being an Igbo or a Yoruba ethnic group was protective for UNLC compared to Fulani/Hausa women. Conclusions A high level of UNLC was found among high-parity women in Nigeria. Access to FP information reduces the risk of UNLC. Expanding FP services would help respond to the expressed desires for contraception among high-parity Nigerian women who want to stop childbearing.